If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(m-3)=4(2m+1)
We move all terms to the left:
3(m-3)-(4(2m+1))=0
We multiply parentheses
3m-(4(2m+1))-9=0
We calculate terms in parentheses: -(4(2m+1)), so:We get rid of parentheses
4(2m+1)
We multiply parentheses
8m+4
Back to the equation:
-(8m+4)
3m-8m-4-9=0
We add all the numbers together, and all the variables
-5m-13=0
We move all terms containing m to the left, all other terms to the right
-5m=13
m=13/-5
m=-2+3/5
| (x-4)^2=x^2+18 | | 3(5–4x)=39 | | 15c=3 | | 3x+4x+20=90 | | x*x-4*4=x*x+18 | | 3m-9=5m-3 | | 7(x-5)+3x=11 | | 5-(6-2x)+5=7x+5(3-x) | | 12×(x-5)=60 | | 2b=3=13 | | 17*3^(3x+1)-4*27^(x-1)+9^(1.5x-1)=243*17-3 | | 0x6=72 | | 2*81^x+(17-2)*36^x=17*16^x | | 9x+4-x=3x–12 | | -3x*(5+-3/x)=0 | | -5x-8=-4x-16 | | 6h+2=4h+10 | | 7u=70u= | | 6x-3(x-4)=4x+8 | | 5-4x/3x^2-x-4=3 | | 4x+8=1–3x | | .x–8=20 | | 109-s=39 | | 1y+7+(-8)+(-5y)= | | (5y-3)^2=7 | | 5/6=m+7/9 | | 1.25x-x=0.25x | | -8z-7;z=3 | | 2x×(x-7)=32 | | 7x-30=7x-28=180 | | 250=2.5(r+r+20) | | 12x−40=20 |